Stained glass artwork - Ghosh, Ayan (2023)
St. Thomas church was inaugurated by the then Governor of Bombay, Charles Boone, on Christmas Day, 1718. At the time, it was referred to as the Church of Bombay. The church was consecrated on 7th June 1816 by Thomas Fanshawe Middleton, the first Anglican Bishop of Calcutta, and dedicated to St. Thomas the Apostle.